Optical signature of symmetry variations and spin-valley coupling in atomically thin tungsten dichalcogenides - Zeng, Hualing; Liu, Gui-Bin; Dai, Junfeng; Yan, Yajun; Zhu, Bairen; He, Ruicong; Xie, Lu; Xu, Shijie; Chen, Xianhui; Yao, Wang; Cui, Xiaodong (Scientific reports, 2013)
We report systematic optical studies of WS 2 and WSe 2 monolayers and multilayers. The efficiency of second harmonic generation shows a dramatic even-odd oscillation with the number of layers, consistent with the presence (absence) of inversion symmetry in even-layer (odd-layer). Photoluminescence (PL) measurements show the crossover from an indirect band gap semiconductor at multilayers to a direct-gap one at monolayers. A hot luminescence peak (B) is observed at ~0.4 eV above the prominent band edge peak (A) in all samples. The magnitude of A-B splitting is independent of the number of layers and coincides with the spin-valley coupling strength in monolayers. Ab initio calculations show that this thickness independent splitting pattern is a direct consequence of the giant spin-valley coupling which fully suppresses interlayer hopping at valence band edge near K points because of the sign change of the spin-valley coupling from layer to layer in the 2H stacking order.